Microbial community characteristics and pathogens detection in Rhipicephalus sanguineus and Haemaphysalis hystricis from Hainan Island, China - Shu, Chang; Intirach, Jitrawadee; Zhou, Yunfei; Gao, Suzhen; Lv, Xin; Jiao, Huisheng; Hu, Yue; Lv, Zhiyue (Frontiers in Microbiology, 2024)
Background: Microbial communities significantly influence the vector capacity of ticks, which, along with tick-borne diseases, pose an increasing global threat. Due to the substantial individual variability caused by various factors, it is essential to assess tick microbial communities and vectorial capacities under different environmental conditions. However, there is a relative scarcity of research on the microbial communities and pathogen transmission of ticks in different physiological states and environmental conditions, especially in Hainan Island, southern China.From 2021 to 2022, we collected 4167 tick samples, grouping them by blood meal status, developmental stage, sex, time, geographical location, and tick species. We selected 128 samples for full-length 16S rRNA sequencing to describe microbial community characteristics and identify potential biomarkers. 772 samples were tested for seven tick-borne pathogens (Rickettsia, Borrelia burgdorferi, Ehrlichia, Anaplasma, Theileria, Babesia, Hepatozoon), and sera from 208 residents of Hainan Island were tested for IgG antibodies against Rickettsia and B. burgdorferi.Results: Blood meal status, developmental stage, sex, time, geographical location, and tick species significantly influenced the microbial communities of ticks. We observed distinct microbial community characteristics across different states. We noted the nonrandom replacement of stable and transient species, with functional differences between parasitic and engorged ticks mainly driven by transient species. Functionally, we observed three distinct response patterns: driven by stable species, transient species, 3 and both together in response to the six factors. We identified 273 potential biomarkers (200 robust core species and 73 robust differential species). Six genera and eight species of pathogens were detected in ticks, with an overall positivity rate of 12.44% (96/772).Among humans, 18.27% (38/208) of serum samples were positive for at least one tickborne pathogen IgG.Our findings indicate that these six factors significantly influence both tick microbial communities and vectorial capacity, with varying effects on vector competence for different pathogens and inconsistent impacts on microbial communities under different conditions. This study supplemented the understanding of tick microbial communities on Hainan Island, assessed the relatively high risk of tick-borne pathogens in the region, and evaluated the impact of these factors on both microbial communities and vectorial capacity.